Mechanical and Barrier Properties of Biocellulose Nata de Coco-Based Edible Film: Influence of Purple Yam (Dioscorea alata) Flour and Glycerol Concentration - Muflihah Ramadhia; Indrastuti, Y. Erning; Ledy Purwandani (CV. Media Digital Publikasi Indonesia, 2023)
Edible films represent biodegradable food packaging. Potential material used as an edible film is biocellulose nata de coco, but flour made from purple yams needs to be added to increase the solubility of composites in water. The purpose of this research was to study the effects of purple yam flour and glycerol concentrations on moisture, ash content, thickness, barrier properties (WVTR), and mechanical properties biocellulose based edible film. Edible films made with the proportion of slurry biocellulose and purple yam flour were 100: 0; 98: 2; 96: 4% and glycerol were added 0, 1, and 2% and aquades was added to the total volume of 200 ml. The suspension is put in a mould and dried in a 40 ° C oven for 24 hours. Increased concentrations of purple yam flour at biocomposite and glycerol reduce tensile strength and modulus of elasticity, increase the thickness of the edible film. Interaction between biocellulose-purple yam flour and glycerol at high concentrations reduced mechanical strength as a result of network integrity disruption. Interaction between biocellulose-purple yam flour and glycerol reduced moisture content but increased ash content. Glycerol concentrations that were too low and high cause antiplastizicer properties that affected the elongation at break and WVTR edible film. This study demonstrated that proportion of biocellulose-purple yam flour 98:2% and glycerol 1% has good potential for producing the edible films